Lower CSF ApoE glycosylation associates with measures of Alzheimer's disease biomarkers. (20th December 2022) - Nedelkov, Dobrin; Meuret, Cristiana; Martinez, Ashley; Hu, Yueming; Smadi, Sabrina; Yassine, Hussein N.
Abstract: Background: The mechanisms of how APOE4 allele (APOE4) increases the risk of Alzheimer's disease (AD) pathology have not been fully elucidated. In cerebrospinal fluid (CSF), apoE is heavily glycosylated but its contribution to AD pathology is not known. The objective of this study was to determine the impact of APOE genotype and cognitive status on the relative abundance of apoE protein isoforms and their specific glycosylation patterns in CSF and plasma. Method: Total glycosylation and ApoE isoform‐specific glycosylation were analyzed in plasma and CSF from a group of older individuals (n = 106) from the USC ADRC cohort, grouped into cognitively normal, with mild cognitive impairment, and with AD dementia. We used a new mass spectrometric immunoassay that simultaneously detects the apoE isoforms and glycoforms (O‐linked GalNAc(‐Sia)‐Gal‐Sia, and various combinations thereof). Result: In heterozygous individuals, the apoE3/E2, E4/E2, and E4/E3 isoform ratios were all significantly lower in plasma compared to CSF. For all individuals, a single O‐linked glycan was observed in plasma, while two glycans (of the same type) per apoE were observed in CSF. The ratio of glycosylated to total apoE was greater in CSF compared to plasma for all apoE isoforms. In CSF, ApoE4 was 35% and 25% less glycosylated (P<0.001) than ApoE2 and ApoE3 carriers respectively. The % of secondary glycosylation was positively correlated with CSF Aβ42 levels (R=0.55, p<0.001) and negatively correlated with CSF total Tau (R=‐0.38, p=0.001). Patients with AD dementia had lower % glycosylation than individuals with MCI (p=0.008). Conclusion: CSF glycosylation is lower in CSF apoE4 isoform and in those with dementia, and correlate with markers of AD pathology. Ongoing experiments are delineating the effects of ApoE glycosylation on its functions. ApoE4 glycosylation may represent a newer target of treatment in AD.